The Effectiveness of Problem-Based Learning Model In Improving Critical Thinking Skills in Science Learning: a Meta-Analysis - Busyairi, Ahmad; Kusuma, Anindita SHM (Universitas Hamzanwadi, 2023)
This study aims to determine the effectiveness of the problem-based learning (PBL) model in improving students' critical thinking skills in science learning. A meta-analysis study was carried out in this study by analyzing 30 scientific articles resulting from previous studies. The selected scientific articles have criteria namely; (1) articles that discuss the effect of applying the PBL model on critical thinking skills in learning science (physics and biology) (2) articles from national and international journals with research locations in Indonesia (3) journals published within the last five years. The data in this study were analyzed by calculating the average effect size from several previous studies and then categorized using the criteria set by Cohen's. The results of data analysis showed that the average effect size for physics subjects was 1.08 while for biology subjects it was 1.06. It can be concluded that the PBL model is effectively used to improve students' critical thinking skills in learning science (physics and biology) with a level of effectiveness in the high category.